The Hegemony of Uken-Toa Socio-Politics in the Regional Head Elections in Aceh Tengah - Efendi, Muhsin; Basri, Hasan; Fahkrurraji, Alzikri; Indah, Yusmika (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The purpose of this study was to investigate the hegemony of Uken-Toa socio-politics in the regional head elections in Central Aceh. In addition, this study also attempted to determine the factors that cause the occurrence of Uken-Toa socio-politics in every election held in Central Aceh. In this study, the researchers focused on the topics of local politics, identity politics, regional elections, and socio-politics. The type of this study was phenomenological and ethnographical research by describing the patterns of values, behavior, beliefs, language, reality, and experiences undergone by individuals. Moreover, the data were collected through interviews, observations, and literature review. Results of this study indicated that the influence of Uken-Toa socio-politics will be always present during the regional head elections in Central Aceh. This means that competition between community groups is unavoidable in the Gayo people. In addition, this practice, which proces actors who represent Belah-Uken and those who represent Belah Toa, greatly affects the victory of the candidates in every regional head election held in Central Aceh. This kind of political practice even has occurred from the past until the current era. Moreover, it has an impact on the system of governance run by the elected regional heads, in this case, the regent and deputy regent of Central Aceh. In other words, this practice indicates how massive a socio-political power is in the local political order of Central Aceh as a political instrument. This Uken-Toa socio-political power in the Gayo community has been formed with long historical, cultural, and political dynamics. This political practice presents the competition between political actors from Belah Uken and Belah Toa, which are influenced by the values of Uken and Toa’s lives. Through this study, the researchers recommend to political elites and the public to avoid Uken-Toa socio-politics to create political harmony and a stable government system. In addition, it is to provide opportunities for other political actors not affiliated with those groups.